PENGEMBANGAN DAN KOMERSIALISASI TEKNIK PENCAIRAN BATUBARA LANGSUNG (DIRECT LIQUEFACTION) DI INDONESIA - Silalahi, Lambok Hilarius (Jurnal Energi dan Lingkungan (Enerlink), 2007)
The latest status of the Coal Liquefaction project in Indonesia which had beenconducted over a decade is discussed. This paper provides some reviews of allactivities that have been made during the past 10 years under the collaborationbetween Japan and Indonesia. Currently, the situation has changed that coalliquefaction has been reconsidered as an important technology which should beimmediately introduced and demonstrated in Indonesia, not only because thecurrent oil price increased, but also in order to reduce the dependency onimported oil. This paper provides some suggestions and consideration on how topromote the Brown Coal Liquefaction (BCL) process toward commercialization inIndonesia. Since coal shares the biggest energy consumption in Indonesia, agreat measure of effective utilization of low grade coal is ultimately important,since almost 70% of the total 104 billion tons of coal resources are classified aslow-rank coal. In view of this situation, the promotion of coal liquefactiontechnology should be more accelerated. The comparison of inland and coastalsite mine-mouth coal lique faction plant is made to confirm the feasibility of bothperspectives for priority implementation.Kata kunci: coal liquefaction, feasibility study, coastal case